Injectable selenium-containing polymeric hydrogel formulation for effective treatment of myocardial infarction - Yang, Cui; Zhu, Chunyan; Li, Yanling; Li, Zibiao; Zhang, Zhenghao; Xu, Jiajia; Chen, Minwei; Li, Runjing; Liu, Shixiao; Wu, Yunlong; Huang, Zhengrong; Wu, Caisheng (Frontiers in Bioengineering and Biotechnology, 2022)
Myocardial infarction (MI) is a serious threat to people’s life and health, which is significantly hindered by effective treatment formulations. Interestingly, our recent endeavour of designing selenium-containing polymeric hydrogel has been experimentally proved to be helpful in combating inflammatory responses and treating MI. The design was inspired by selenium with anti-inflammatory and anti-fibrosis activities, and the formulation could also serve as a support of myocardial tissue upon the failure of this function. In details, an injectable selenium-containing polymeric hydrogel, namely, poly[di-(1-hydroxylyndecyl) selenide/polypropylene glycol/polyethylene glycol urethane] [poly(DH-SE/PEG/PPG urethane)], was synthesised by combining a thermosensitive PPG block, DH-Se (which has oxidation-reduction properties), and hydrophilic PEG segments. Based on the established mouse model of MI, this formulation was experimentally validated to effectively promote the recovery of cardiac function. At the same time, we confirmed by enzyme-linked immunosorbent assay, Masson staining and Western blotting that this formulation could inhibit inflammation and fibrosis, so as to significantly improve left ventricular remodelling. In summary, a selenium-containing polymeric hydrogel formulation analysed in the current study could be a promising therapeutic formulation, which can provide new strategies towards the effective treatment of myocardial infarction or even other inflammatory diseases.